2017
DOI: 10.1111/joor.12579
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with occlusal scheme of conventional complete dentures: A randomised clinical trial (part I)

Abstract: Summary Background Occlusal scheme can affect denture retention, stability, occlusal force distribution, aesthetics, masticatory function, patient comfort and general patient satisfaction with dentures. Objectives This study aimed to compare the patient satisfaction with 3 types of complete denture occlusion including fully bilateral balanced occlusion (FBBO), newly presented buccalised occlusion (BO) and lingualised occlusion (LO). Methods In this parallel randomised clinical trial, new conventional complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 18 publications
(77 reference statements)
1
39
1
1
Order By: Relevance
“…All of the studies reported the BBO occlusion scheme; of these, 7 studies compared BBO with CG, 9 compared BBO with LO, and 3 compared BBO with ZD . Most of studies were considered crossover design, while 6 other studies were not considered crossover design . In crossover design, the most of studies made a new set of dentures to evaluated occlusion effect .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the studies reported the BBO occlusion scheme; of these, 7 studies compared BBO with CG, 9 compared BBO with LO, and 3 compared BBO with ZD . Most of studies were considered crossover design, while 6 other studies were not considered crossover design . In crossover design, the most of studies made a new set of dentures to evaluated occlusion effect .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies found positive effect in terms of satisfaction or quality of life for LO, perhaps because enables more efficient bolus penetration than BBO, or because LO presents less occlusal interference and surface contacts between the maxillary and mandibular teeth and, consequently, fewer mandibular denture loadings and dislodging during lateroprotrusion movements . Furthermore, LO should be considered a favorable occlusal scheme because present lower physical pain compared to BBO, especially for patients with a severely reabsorbed mandibular alveolar ridge (<20 mm), because it provides better mandibular denture retention and a lower chance of pain than BBO . However, in this study, the authors used porcelain teeth in their BBO scheme and hard resin teeth in their LO scheme; this may have influenced the results, as porcelain shows a higher modulus of elasticity than resin and thus contributes to a pressure increase in the residual ridge …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on balanced occlusal schemes have reported variable results. Some such studies indicated the superiority of lingualised occlusion (LO) compared with fully bilateral balanced occlusion (FBBO) . On the other hand, a few studies found similar results for LO and FBBO .…”
Section: Introcuctionmentioning
confidence: 99%